An adaptive fuzzy logic controller by sliding mode control method for DC/DC converter - Khaehintung, Noppadol; Kunakorn, Anatawat; Aorpimai, Manop; Sirisuk, Phaophak (My University, 2005)
This paper presents the design of an adaptive fuzzy logic controller for DC/DC buck converters. The proposed controller uses a sliding mode control mechanism to improve the performance of a conventional buck converter. Despite of the nonlinear behavior of the converter, the performance of the closed-loop control system can be considerably improved compared to the results gained from other previously proposed schemes, such as the adaptive fuzzy logic controller by back propagation algorithm. This claim is obviously shown by the simulation and experimental results both in regulating and tracking modes. © 2005 IEEE.
Keywords: Adaptive fuzzy logic controller; Back propagation algorithm; Component; DC/DC buck converter; Sliding mode control